Claim on future interest as matrimonial property: special reference to Malaysia Shari’ah courts - Abdul Ghadas, Zuhairah Ariff; Ibrahim, Norliah; Imam-Tamim, Mohd Kamal (Herald National Academy of Managerial Staff of Culture and Arts, 2018)
In both the Civil and Shari’ah courts, the test applied in deciding rights and proportion of the divorced parties for matrimonial property is the “contribution test” whereby if both parties contributed to the acquisition of the property than both parties shall have rights on the property. The proportion shall be decided based on the fraction which each parties contributed to the property. It is observed that the contribution test could be effectively applied for tangible assets such as houses, land, vehicles, jewelries and saving which are personally owned by the parties. However, when it comes future interest, the contribution test could not be applied until the court is willing and/able to determine the rights to claim for the future interest. This research applies legal research methodology which focuses on statutory and case law analysis